Answers

  • Brainly User
2015-12-30T22:12:12+08:00
In arithmetic sequence, the difference between any consecutive terms are equal.

First, find the difference between the consecutive terms. In subtracting polynomials, change the sign of each term of subtrahend, then proceed to addition rule,

The sequence:
5k-3,  k+2,  3k-11

a)  (k+2) - (5k-3)
     =  (k+2) + (-5k+3)
     -4k + 5

b)  (3k-11) - (k+2)
     = (3k-11) + (-k-2)
     = 2k - 13

Equate the result (difference between the terms):
-4k + 5 = 2k - 13
-4k - 2k = -13 -5
-6k = -18
-6k/-6 = -18/-6
k = 3

ANSWER: The value of k is 3.

Check:
5k - 3
= 5(3) - 3
= 15 - 3
= 12

k + 2
= (3) + 2
= 5

3k - 11
= 3(3) - 11
=  9 - 11
=  - 2

The arithmetic sequence:
12, 5, -2

The difference between consecutive terms should be common/equal:
-2 - 5 = -7
5 - 12 = -7

The sequence is decreasing, and the difference between terms is -7.  


0